Potensi Umbi Porang Sebagai Bahan Baku Beras Tiruan Rendah Kalori - Ayatullah, Maulana Wahyu; Arbin, Alfiandi; Mohi, Sarahwati; Tansala, Gabriela Stefany (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Porang is a tuber plant from the Amorphophallus muelleri species, Porang is a plant that is tolerant of shade. Porang can grow on any type of soil at an altitude of 0 to 700 meters above sea level. Porang plants have strategic value to be developed, because they have great potential for export. Porang tubers contain Glucomannan as a basic ingredient in the food industry and have a low calorie value and are sugar-free. To support national food security, it is necessary to diversify the types of staple foods in the form of imitation rice so porang tubers have the potential to be processed into low-calorie rice, the potential for increasing food production is very possible if carried out in accordance with proper governance to develop the agricultural industry.